United Nations Disarmament Yearbook 2022 - United Nations Office for Disarmament Affairs (United Nations, 2023)
The United Nations Disarmament Yearbook 2022 is the 47th volume and it summarizes developments and trends in 2022 on key issues of multilateral consideration at the international and regional levels. It reviews the activities of the General Assembly, the Conference on Disarmament and the Disarmament Commission. The yearbook also contains a timeline that highlights events in multilateral disarmament in 2022.